Identification of clinical phenotypes of Alzheimer's disease through the gut microbiota: Neuropsychology/Neuropsychological correlates of physiologic markers of cognitive decline/Dementia. (7th December 2020) - Marizzoni, Moira; Cattaneo, Annamaria; Mirabelli, Peppino; Luongo, Delia; Mombelli, Elisa; Salvatore, Marco; Frisoni, Giovanni B.
Abstract: Background: The genetic, clinical and anatomical presentation of Alzheimer's disease (AD) is extremely heterogenous. Although increasing evidences show that alterations in the gut microbiota (GMB) composition are involved in AD, their contribution to AD pathology remain unclear. The aim of this study is to evaluate whether disease‐specific alterations of the microbiome are present in patients with AD pathology and can identify individuals with peculiar clinical features. Method: Sixty‐two cognitive impaired subjects underwent Florbetapir amyloid PET and stool collection. Brain amyloidosis was measured with standardized uptake value ratio versus cerebellum (SUVRs) in the frontal, parietal, temporal, anterior cingulate, posterior cingulate and precuneus regions of interest. Amyloid positivity was defined as global PET florbetapir SUVR>1.11. Bacterial composition of fecal samples was inferred using 16S metagenomic sequencing, analyzed with QIIME 2 (Quantitative Insights into Microbial Ecology, https://qiime2.org/ ). We first compared amyloid negative (Amy‐) and positive (Amy+) patients with respect to GMB‐specific profiles. We then applied Principal Component Analysis (PCA) on those taxa found differentially abundant in Amy+ and Amy‐. Result: Despite a similar GMB structure (Unweighted and weighted Unifrac, p>0, 05) of Amy+ (n=29) and Amy‐ (n=33), taxonomic comparison showed that Amy+ were mainly characterized by rare genera. PCA identified a small subgroup of 6 Amy+ with lower amyloid SUVR uptake in the temporal cortex (p=0, 009) and lower cognitive deficits, as showed by better performance at MMSE, ADAScog, logical memory, Rey auditory verbal learning test, Raven's progressive matrices test and Functional Activities Questionnaire (p<0.044) compared to the other Amy+ patients. Amyloid SUVR uptake in the temporal cortex was negatively associated with logical memory, Rey auditory verbal learning test, Raven's progressive matrices test and Functional Activities Questionnaire (moderate: rho£0.44, p£0.047) and MMSE (weak: rho=0.36, p=0.076) as well as negatively associated with FAQ (moderate: rho=0.47, p=0.010) in the whole Amy+ group. Conclusion: Despite the small sample size, this study suggests that distinctive bacterial signatures might be associated with specific clinical AD phenotypes.